1999
DOI: 10.1128/jb.181.23.7206-7211.1999
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization of SusG, an Outer Membrane Protein Essential for Starch Utilization by Bacteroides thetaiotaomicron

Abstract: Results from previous studies had suggested that Bacteroides thetaiotaomicron utilizes starch by binding the polysaccharide to the bacterial surface and subsequently degrading the polymer by using cell-associated enzymes. Most of the starch-degrading activity was localized to the periplasm, but a portion appeared to be membrane associated. This raised the possibility that some breakdown might occur in the outer membrane prior to exposure of the polysaccharide to the periplasmic polysaccharide-degrading enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 21 publications
2
60
0
1
Order By: Relevance
“…They are described as secreted catalytic enzymes while Sus-like systems are multiprotein complexes associated with the outer membrane of Gram-negative bacteria. They can bind and degrade specific substrates and presumably operate an energy-dependent import of the processed molecules (Shipman et al, 1999;Cho and Salyers, 2001;Schauer et al, 2008;Martens et al, 2009). In conclusion, the genome of Cc5 does not encode any classical virulence system (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…They are described as secreted catalytic enzymes while Sus-like systems are multiprotein complexes associated with the outer membrane of Gram-negative bacteria. They can bind and degrade specific substrates and presumably operate an energy-dependent import of the processed molecules (Shipman et al, 1999;Cho and Salyers, 2001;Schauer et al, 2008;Martens et al, 2009). In conclusion, the genome of Cc5 does not encode any classical virulence system (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Bacterial lipoproteins are membrane proteins present both in Gram-negative and Gram-positive bacteria. In Bacteroidetes some lipoproteins, including the hydrolase (SusG, GH13) from SUS systems are known to be transported to the outer surface of the outer membrane (Shipman et al, 1999). In E. coli the lipoproteins are anchored either to the inner or to the outer membrane, and oriented towards the periplasmic space (Tokuda and Matsuyama, 2004).…”
Section: Functional Potential Of the Hydrolases In E Colimentioning
confidence: 99%
“…4 SusG is a GH13 amylase that is central to starch utilization by the human gut commensal Bacteroides thetaiotaomicron. 5 SusG displays substrate flexibility for diverse a-glucans, including amylopectin, pullulan, and cyclodextrins, yet it invariably hydrolyzes a1,4-linkages. 6 Our previous work revealed that SusG displays an atypical domain organization among GH13 members, which in addition to the canonical A, B, and C domains, includes the insertion of a unique carbohydrate binding module (CBM) family 58 into the middle of the B domain which is located between b3 and a3 of the catalytic A domain.…”
Section: Introductionmentioning
confidence: 99%